Violence and mental disorders. A retrospective study of people in charge of a community mental health center. (July 2016) - Pinna, Federica; Tusconi, Massimo; Dessì, Claudio; Pittaluga, Giuseppe; Fiorillo, Andrea; Carpiniello, Bernardo
Abstract: Background: Numerous studies conducted in inpatient settings have highlighted how mental disorders are associated with an increased risk of violence, particularly during acute phases. However, to date a more limited number of studies have been performed to assess the risk of violence in outpatients, particularly in Italy. The present study aims to evaluate the prevalence of violent events in a sample of patients in charge of a community mental health center in Italy. Methods: Based on data obtained from standardized clinical records, a retrospective study was undertaken to investigate acts of violence (physical aggression only) in a total of 678 patients (Males = 308, 45.4%) in charge of a university mental health center; patients were mainly affected by anxiety disorders (30.7%), depressive disorder (17.2%), bipolar disorder (18.3%) and schizophrenia or other psychotic disorders (25.0%). Results: 27.6% of the sample had committed at least one act of violence during their lifetime, 10.5% over the previous year. 56.7% of those who committed violence acts had acted violently twice or more during their lifetime. A significant association of lifetime violence was found with gender (male), younger age, low education, unemployment, living with parents. With regard to diagnosis, a significant association was found with schizophrenia and other psychotic disorders, personality disorders, mental retardation, and comorbidity between two or more psychiatric disorders. Violence was moreover associated with early age at onset and at first psychiatric treatment, longer duration of the disorder, previous hospital admissions, previous violent events. Conclusion: Violent behavior is relatively common among outpatients.